Respuesta :
[tex](-\frac{2}{3}x)(3y)(-2x) =\\\\ (-2xy)(-2x) =\\\\\boxed{\bf{4x^2y}}[/tex]
The coefficient is 4.
The coefficient is 4.
Answer:
The coefficient of give expression is 4.
Step-by-step explanation:
The given expression is
[tex](-\frac{2}{3x})(3y)(-2x)[/tex]
It can be written as
[tex](-\frac{2}{3x})(3y)(-2x)=\frac{-2\times 3y\times (-2x)}{3x}[/tex]
[tex](-\frac{2}{3x})(3y)(-2x)=\frac{12xy}{3x}[/tex]
Now cancel out the common factors.
[tex](-\frac{2}{3x})(3y)(-2x)=4y[/tex]
The simplified form of the given expression is 4y.
Therefore the coefficient of give expression is 4.